Yes‐associated protein mediates angiotensin II‐induced vascular smooth muscle cell phenotypic modulation and hypertensive vascular remodelling. (29th August 2018) - Lin, Maohuan; Yuan, Woliang; Su, Zizhuo; Lin, Caina; Huang, Tucheng; Chen, Yangxin; Wang, Jingfeng
Abstract: Objectives: Yes‐associated protein (YAP) has been reported to regulate cell proliferation and differentiation. We aimed to characterize the role of YAP in angiotensin II (Ang II)‐induced hypertensive vascular remodelling (HVR) and vascular smooth muscle cells (VSMCs) phenotypic modulation and to explore the underlying mechanisms. Materials and methods: An HVR rat model was established by continuous Ang II infusion for 2 weeks. Western blotting, qRT‐PCR, and confocal microscopy were conducted to assess YAP expression. YAP‐shRNA interfering plasmid and adenovirus were constructed to knock down YAP. We used cell proliferation and migration assays, accompanied by pathway inhibitors, to evaluate the biological function and underlying mechanisms. Results: Ang II upregulated YAP expression in the media of carotid artery; however, in vivo YAP silencing significantly mitigated HVR, independent of the blood pressure level. Ang II upregulated YAP expression and promoted YAP nuclear accumulation in a dose‐ and time‐dependent manner in rat VSMCs. YAP knockdown ameliorated Ang II‐induced VSMCs phenotypic modulation. The regulation of YAP by Ang II could be blocked by pretreatment with angiotensin receptor type 1 antagonist losartan or F‐actin depolymerizing agent latrunculin B but not the AT2R antagonist PD 123319. Disrupting the YAP‐TEA domain (TEAD) interaction with verteporfin inhibited Ang II‐induced VSMCs phenotypic modulation. Conclusions: Yes‐associated protein mediated angiotensin II‐induced VSMCs phenotypic modulation and vascular remodelling. YAP is a potential therapeutic target for HVR beyond blood pressure control.